Coffee and Alzheimer's Disease: Reviewing the Neuroprotective Effects of Bioactive Compounds - Katarzyna Madyniak; Piotr Ciecierski (Quality in Sport)
Alzheimer's disease (AD) is a common neurodegenerative disorder primarily managed with symptomatic treatments. Coffee, a popular beverage, contains bioactive compounds like caffeine, chlorogenic acid, quercetin, trigonelline, caffeic acid, and kaempferol, which may offer neuroprotective benefits. These compounds could potentially address AD-related pathologies such as amyloid-beta accumulation, tau hyperphosphorylation, oxidative stress, and inflammation. This review explores the neuroprotective potential of coffee's bioactive components in AD.